At-Risk Youth in the Context of Current Normality – Psychological Aspects - Hlad, Ľubomir; Konečná, Irena; Žalec, Bojan; Majda, Peter; Ionescu, Tiberius Constantin; Biryukova , Yulia Nickolaevna (Journal of Education Culture and Society, 2022)
Aim. At-risk individuals have many forms, often it is the two opposing sides of a personality which can ultimately implement risky behaviour only to accept an individual into a peer group.Concept. The risky behaviour of young people and children currently associated with a  consumer society aggravated by the pandemic situation Covid-19 is the subject of interest in professional as well as scientific research of various professionals who work in different areas of life.Methods. This study deals with the risks, social, but also individual consequences of at-risk youth, which occur at all levels of society. In the study, we proceeded in an analytical-synthetic way, interpreting and ascertaining the results of various other scientific and professional studies by foreign authors who deal with the given issue.Results. The study confirms that risky behaviour requires a constant approach to educating a young person through not only the family but also the school environment, which allows a new perspective on risky youth behaviour.  However, it is very important to integrate young people into society to see the risks of their behaviour not only for themselves. but for a narrower or wider community.Conclusion. The scientific articles and contributions offered in this study point out the risky behaviour of young people, the risks of behaviour not only for individuals but also for groups, it points out the possible causes, reasons, but also consequences of risky behaviour.